Transcatheter arterial embolisation in the management of postpartum haemorrhage. (18th April 2012) - Rehal, A; Munawar, S; Bolia, A; Singhal, T
Abstract : Trauma to the lower genital tract is one of the important causes of primary post partum haemorrhage (PPH) leading to significant short and long term morbidity. Operative vaginal delivery is a recognised cause of cervical and vaginal laceration. The cornerstone of the management of PPH secondary to genital tract injury remains haemostatic suturing of the bleeding vessels. However, in difficult cases this may not always be possible due to difficulties regarding accessibility and potentially unsuccessful haemostasis. An emerging radiological technique which is increasingly gaining recognition is pelvic transcatheter arterial embolisation (TAE). This is becoming a valuable asset in the management of PPH and has been reviewed extensively in the literature. We present a case in which TAE was successfully used to arrest bleeding from vaginal trauma caused by operative vaginal delivery despite failed conservative and multiple surgical interventions, together with a review of the current literature. Data from 30 articles was analysed. Our results support the success rate in the literature of pelvic TAE in stopping bleeding from PPH (95.3%). Major complications identified included vesicovaginal fistula, cervical and vaginal necrosis, right buttock claudication and a segmental small bowel infarction. Menstruation resumed in all patients within 60 months. With the use of this case report, we conclude that pelvic TAE is an option to be considered in controlling traumatic PPH, with relatively few complications and no obvious detrimental effects on future menstruation. Long term data is needed with regard to future fertility.